2021
DOI: 10.1155/2021/8820216
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of SD-OCT Detectable Hyperreflective Foci in Diabetic Macular Edema Patients after Therapy with Anti-VEGF Agents and Dexamethasone Implants

Abstract: Purpose. Diabetic macular edema (DME) is the most common cause of blindness in the working-age population. Spectral-domain optical coherence tomography (SD-OCT) allows detection and monitoring of the edema and a detailed analysis of the retinal structure. Hyperreflective foci (HF) are small, circumscribed lesions on OCT, and their origin is yet to be determined. Our study was aimed to shed light on HF pathophysiology, by analyzing their number and location in DME patients at baseline and after therapy. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…Our results agree with other studies [ 4 , 30 , 31 ] in which a better morphological response to intravitreal anti-VEGF and steroids was associated with the presence of HRF. In addition, a greater HRF reduction after DEXi compared with anti-VEGF treatment has been documented [ 28 , 32 , 33 ], confirming the HRF as a biomarker of inflammatory DME pattern [ 4 , 5 , 34 ].…”
Section: Discussionmentioning
confidence: 82%
“…Our results agree with other studies [ 4 , 30 , 31 ] in which a better morphological response to intravitreal anti-VEGF and steroids was associated with the presence of HRF. In addition, a greater HRF reduction after DEXi compared with anti-VEGF treatment has been documented [ 28 , 32 , 33 ], confirming the HRF as a biomarker of inflammatory DME pattern [ 4 , 5 , 34 ].…”
Section: Discussionmentioning
confidence: 82%
“…In the SD-OCT scan they are seen as tiny dense particles in the outer- and inner retinal layers with greater reflectivity than the retinal pigment epithelium (RPE). Their prevalence has been related to the progression of atrophy in age-related macular degeneration [ 44 ], to the activity of diabetic retinopathy [ 45 , 46 , 47 ], macular telangiectasia type 2 (MacTel) [ 48 ] or Morbus Coats [ 49 ], but also to the extent of ischemia in retinal vein occlusion [ 50 ], to the progression of degeneration in RP [ 38 , 39 , 40 , 41 ], as well as to the progression of atrophy in Stargardt disease [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suppose that the HRF represents an inflammatory component like microglia or migrated RPE and/or the extravasation of lipoproteins following the breakdown of the blood-retinal barrier [ 53 , 54 ]. It has been shown that HRF foci are also a predictive marker of the final visual outcome in diseases like retinal vein occlusion [ 50 ], diabetic retinopathy [ 46 ], polypoidal choroidal vasculopathy [ 55 ], neovascular age-related macular degeneration [ 55 ], but also in degenerative diseases like RP [ 38 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 0.7 mg intravitreal DEX implant Ozurdex® (Allergan, Inc.) was designed to deliver medication to the retina and could maintain the drug concentration in the vitreous body for up to 6 months 3 . Several research groups thereafter initiated head-to-head clinical trials to compare the efficacy of anti-VEGF therapy and Ozurdex therapy 14 58 . BEVORDEX, the first RCT to assess this, reported that Ozurdex therapy was not inferior to anti-VEGF therapy in terms of visual acuity (VA) changes and that it led to superior anatomical outcomes compared with anti-VEGF therapy at the primary endpoint 35 .…”
Section: Introductionmentioning
confidence: 99%